Analysis of Physical and Mental Health of Prospective Spouses Regarding Marriage Stress in the Ciruas Health Center Work Area, Serang Regency, Serang - Siti Ahdah; Retno Widowati; Lisa Trina Arlym (Rajaki of Tulip Medika Publisher, 2025)
Marriage is a crucial phase in life that requires optimal physical and mental readiness. High levels of stress in prospective spouses can impact their health, relationships, and the quality of their married life. This study aims to analyze the effect of physical and mental health checks on the stress levels of prospective spouses in Ciruas District, Banten Province. The study design used a quantitative approach with a quasi-experiment and a qualitative approach through in-depth interviews. A sample of 132 people was determined using the Slovin formula and the purposive sampling technique. The variables studied included blood pressure, BMI, hemoglobin levels, infectious diseases, and mental conditions based on the GAD-7. The intervention was carried out in the form of premarital health checks and education. Research Results: Quantitatively, the average stress score of prospective spouses before the intervention was 8.45 and decreased to 6.13 after the intervention, indicating a statistically significant improvement (p = 0.000). Most respondents (97%) were in good physical condition, and mental examinations showed an increase in psychological stability after counseling. Qualitative data revealed that partner support, perceptions of test results, and counseling experiences influenced stress reduction, while barriers included limited access to services, concerns about test results, and low health literacy. This study concluded that physical and mental health screenings significantly reduced stress levels for prospective spouses.